2002
DOI: 10.1021/ja0274960
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of Heme to β- and δ-Biliverdin byPseudomonas aeruginosaHeme Oxygenase as a Consequence of an Unusual Seating of the Heme

Abstract: The origin of the unusual regioselectivity of heme oxygenation, i.e. the oxidation of heme to delta-biliverdin (70%) and beta-biliverdin (30%), that is exhibited by heme oxygenase from Pseudomonas aeruginosa (pa-HO) has been studied by (1)H NMR, (13)C NMR, and resonance Raman spectroscopies. Whereas resonance Raman indicates that the heme-iron ligation in pa-HO is homologous to that observed in previously studied alpha-hydroxylating heme oxygenases, the NMR spectroscopic studies suggest that the heme in this e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
196
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 96 publications
(214 citation statements)
references
References 59 publications
13
196
0
Order By: Relevance
“…The low activation of entropy of the wild-type pa-HO suggests that the transition state is highly ordered, and this stabilization could be provided in the form of a protein-protein interaction, which is consistent with the gain in entropy observed for the pa-HO-mutants and BphO. However, an exact interpretation of these effects will require a more extensive study with a larger set of mutants at these and other positions in and around the heme pocket of both PhuS and pa-HO.Previous observations suggested that at neutral pH the heme-PhuS and heme-pa-HO complexes are respectively (15,19). Therefore, changes in both the spin-state and axial heme coordination must occur during the transfer reaction.…”
supporting
confidence: 77%
See 2 more Smart Citations
“…The low activation of entropy of the wild-type pa-HO suggests that the transition state is highly ordered, and this stabilization could be provided in the form of a protein-protein interaction, which is consistent with the gain in entropy observed for the pa-HO-mutants and BphO. However, an exact interpretation of these effects will require a more extensive study with a larger set of mutants at these and other positions in and around the heme pocket of both PhuS and pa-HO.Previous observations suggested that at neutral pH the heme-PhuS and heme-pa-HO complexes are respectively (15,19). Therefore, changes in both the spin-state and axial heme coordination must occur during the transfer reaction.…”
supporting
confidence: 77%
“…The increase in the activation energy for heme transfer from holo-PhuS to the pa-HO mutants relative to the native protein is most likely due to the loss of favorable binding or interaction between PhuS and pa-HO. The pa-HO mutants introduced heme propionate interactions required for α-regioselective specificity (pa-HO-N19K/F117Y) as in other characterized HO enzymes and additionally removed residues that stabilize the δ-regioselective heme seating (pa-HO-N19K/ F117Y/K132A and pa-HO-N19K/F117Y/K34A) (19). In addition, these amino acid replacements are located on the heme binding face of pa-HO and, as well as stabilizing the bound heme, are located such that in the apo-pa-HO they may provide additional electrostatic or hydrogen-bonding interactions with the holo-PhuS (22).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 The HOs identified for a number of pathogeneic bacteria 11-13 appear to have as their major role the "mining" of iron to infect a host. 3, 5 Two such HOs of interest here are Neisseria meningitidis, NmHO (also called HemO 12,14,15 ) and Pseudomonas aeruginosa, PaHO 13,16,17 . A common mechanism, worked out on the mammalian HOs, appears operative in the various HOs.…”
Section: Introductionmentioning
confidence: 99%
“…1). The unusual production of ␤-and ␦-BV was shown to be due to an unusual seating of the substrate heme in the active site pocket of PigA (9). The purpose for the production of these BV isomers and their fate in P. aeruginosa, however, is currently unknown.…”
mentioning
confidence: 99%